A SYSTEMATIC LITERATURE REVIEW ON THE INTEGRATION OF AI IN HIGHER EDUCATION - J. Priyanto Widodo; Hariyanto Hariyanto; Anggun Purnomo Arbi (Widya Mandala Surabaya Catholic University, 2024)
This research presents a literature review on the integration of artificial intelligence (AI) in the higher education. This study used a systematic literature review research design. The findings show that AI has the capacity to improve student engagement, critical thinking skills, and teaching effectiveness. In addition, AI contributes to improving language and journalistic writing skills, as well as creating a dynamic learning environment. However, there are moral as well as ethical challenges. These include privacy, algorithm fairness, and over-reliance on this technology. This research ultimately highlights the importance of strategic and ethical application of AI in the context of higher education. It also highlights that there is a need for further research into the long-term impact of the integration of these technologies. The development of more comprehensive AI models and theories is also needed to ensure more responsible and equitable use.